Interaksi Teman Sebaya dan Dampaknya Terhadap Minat Belajar Peserta Didik Mata Pelajaran Pendidikan Agama Islam Siswa Kelas 5 Di SDN 5 Limboto - Hardiyanti Mahmud, Yane; Cilan Idrus (JAMBURA Elementary Education Journal, 2025)
This study aims to describe peer interaction and its impact on students’ learning interest in the Islamic Religious Education (PAI) subject in Grade 5 at SDN 5 Limboto, Gorontalo Regency. Using a descriptive qualitative approach, data were collected through direct observation. The results show that peer interaction has a significant influence on learning interest, both positively and negatively. Positive interactions, such as group study, discussions, and moral and spiritual support, enhance motivation, understanding of Islamic Religious Education concepts, and the internalization of religious values. On the other hand, negative interactions such as social pressure, exclusivity, and unsupportive behavior toward religious studies hinder participation, lower self-confidence, and reduce interest in learning. The teacher acts as a facilitator in managing students’ social dynamics to remain inclusive and constructive through strategies such as heterogeneous study groups, collaborative religious projects, and personal approaches. In conclusion, peer interaction plays an important role in shaping students’ interest in Islamic Religious Education, thereby requiring appropriate social management in the classroom.